Ambiguous agency in the vulnerable trafficked body: reading Sanusi’s Eyo and Unigwe’s On Black Sisters’ Street - Ligaga, Dina (Tydskrif vir Letterkunde, 2019)
The narrativization of the trafficked body in the novels of Abidemi Sanusi and Chika Unigwe allows for a contemplation of Europe in African migrant imaginaries as both promise and failure. Sanusi’s Eyo is a narrative of a ten-year-old girl who is trafficked to the United Kingdom as a human sex slave. The novel draws attention to the tensions that define her being/unbeing in Europe and beyond, even after a brave escape from her traffickers. This precarious existence is enhanced in Chika Unigwe’s On Black Sisters’ Street, whose main characters exist in Europe selling their bodies while existing in states of continuous vulnerability. In reading these two novels side by side, this article explores the discursive meanings of trafficked bodies and how traumatic existence allows for an engagement with Europe as illusory in the imaginaries of African women who cross borders into Europe. The article argues that while the female characters are vulnerable, they retain an ambiguous agency contained within their ability to survive and remain resilient in the face of atrocities for borders crossers. The narrative form of the novel allows for an exploration of what this agency looks like in the face of extreme vulnerability.